2017
DOI: 10.1371/journal.pone.0182956
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, associated comorbidities and coping strategies in French community pharmacies—BOP study: A nationwide cross-sectional study

Abstract: BackgroundWork-related stress and burnout syndromes are unfortunately common comorbidities found in health professionals. However, burnout syndrome has only been partly and episodically assessed for community pharmacists whereas these professionals are exposed to patients’ demands and difficulties every day. Prevalence of burnout, associated comorbidities and coping strategies were assessed in pharmacy teams (pharmacists and pharmacy technicians) in French community pharmacies.MethodsThis online survey was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 43 publications
3
45
1
3
Order By: Relevance
“…Our analysis demonstrated no significant differences in burnout levels (both for the three specific dimensions and the overall index) of the investigated men and women, according to previous research performed among a sample of community pharmacists in Ankara [26]. In contrast, other studies demonstrated that men suffer significantly more of burnout syndrome than women and that women are at higher risk of mental disorders, depression, anxiety, and psychosomatic illnesses and men seem to suffer more from higher levels of stress [27,28]. In addition, previous researches evidenced that female physicians present a lower risk of depersonalization and a higher risk of emotional exhaustion with respect to males [29,30].…”
Section: Discussioncontrasting
confidence: 51%
“…Our analysis demonstrated no significant differences in burnout levels (both for the three specific dimensions and the overall index) of the investigated men and women, according to previous research performed among a sample of community pharmacists in Ankara [26]. In contrast, other studies demonstrated that men suffer significantly more of burnout syndrome than women and that women are at higher risk of mental disorders, depression, anxiety, and psychosomatic illnesses and men seem to suffer more from higher levels of stress [27,28]. In addition, previous researches evidenced that female physicians present a lower risk of depersonalization and a higher risk of emotional exhaustion with respect to males [29,30].…”
Section: Discussioncontrasting
confidence: 51%
“…Regarding professional stressors, respondents' comments ( Table 3) included both external and individual factors, which is consistent with previously published literature. 1,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Regarding the question about what interferes with respondents' ability to meet expectations in their professional lives, 2 other themes emerged, namely (1) health and (2) striving for perfection. Comments related to health, often times related to not having time to maintain a healthy lifestyle, being lonely, suffering anxiety and depression, and mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…There is an abundance of reported research that describes pharmacists' job stress, job satisfaction, professional commitment, work motivation, work overload, burnout, and job turnover. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] There is evidence that stress levels are rising for student pharmacists 38,39 and pharmacy residents as well. [40][41][42][43][44] Recent literature showed that 61% of clinical pharmacists practicing in hospital settings reported signs of burnout in 2016, 33 and 53% of health-system pharmacists exhibited high burnout on at least 1 subscale of the Maslach Burnout Inventory Human Services Survey (MBI-HSS).…”
mentioning
confidence: 99%
See 2 more Smart Citations